Health messages, middle-aged women and the pleasure of play. Issue 1 (1st January 2017) - Lenneis, Verena; Pfister, Gertrud
ABSTRACT: Western societies glorify youth and consider middle age as the onset of deterioration. The prevalent discourses on middle-aged women focus primarily on negative developments in their lives such as increased health risks after menopause. Little is known, however, about the lived experiences of this age group. In this article, we share information about the health- and ageing-related attitudes of women aged 45–55 years who took part in a physical activity intervention in Denmark. Drawing on Foucault's concepts of disciplinary power and governmentality, we explored via 15 semi-structured interviews the women's reasons for participation and their experiences with playing a team game. The interviews revealed that they had internalized the messages of 'healthy ageing' and felt guilty about their previous inactive lifestyle. However, their participation was also influenced by changing life circumstances. Now they had time to exercise and, contrary to previous experiences, they found that playing games provided pleasure.